Airway Management of a Child with Penetrating Neck Injury: A Case Report - Yadav, Ashish; Saini, Aman Kaur; Komal; Raheja, Dhruv (Asian Journal of Medical Research, 2021)
Injuries of upper airway can lead to hazardous consequences. After penetrating trauma these injuries may lead to hoarseness of the voice which can be managed conservatively or it can also lead to respiratory distress for which emergency tracheostomy is required. 18 Year old female child suffered from penetrating neck injury while playing with chain of cart. In presence of respiratory distress and hemodynamic instability immediate surgical exploration and securing airway may be required. Managing the airway can be a nightmare for any anaesthesiologist. Fibreoptic bronchoscopy aids to assess the airway injuries and is the safest possible option but cannot be used in uncooperative patients and children. Securing the airway in awake patients is although the safest option in such situations.